2015
DOI: 10.4238/2015.january.23.7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pH effects on genomic integrity in adipose-derived mesenchymal stem cells using the comet assay

Abstract: ABSTRACT. The use of mesenchymal stem cells (MSCs) in experimental, clinical, and therapeutic trials has grown in recent years. However, the issue remains of whether these procedures are completely safe for transplant patients. Therefore, this study was designed and carried out with the aim of evaluating two different comet assay protocols for genomic damage pattern analysis in MSCs derived from adipose tissue. The analyzed and interpreted results suggest that genetic testing is needed to support clonal expans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The MSCs used in the present study were characterized by adipogenic, osteogenic and chondrogenic differentiation. These results are consistent with previous studies (Bagnaninchi et al , 2011; Pendleton et al , 2013; Vieira et al , 2014 ; Hermeto et al , 2015 ), as was the efficiency of the selection and expansion methods used here.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The MSCs used in the present study were characterized by adipogenic, osteogenic and chondrogenic differentiation. These results are consistent with previous studies (Bagnaninchi et al , 2011; Pendleton et al , 2013; Vieira et al , 2014 ; Hermeto et al , 2015 ), as was the efficiency of the selection and expansion methods used here.…”
Section: Discussionsupporting
confidence: 94%
“…At the end of the respective culture periods, media were removed and cells were fixed in paraformaldehyde for 1 h. Adipogenic and osteogenic differentiation were assessed by staining with Oil Red O and Alizarin Red S, respectively. Chondrogenic differentiation was assessed by submitting the pellet to conventional histological processing and staining with toluidine blue ( Hermeto et al , 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…This result indicated that genotoxic lesions observed in the comet assay were not fixed in the DNA as a permanent DNA damage. Rather, lesions detected by this comet assay, including single- and double-strand breaks, alkaline-labile sites, crosslinks, excision repair sites, methylation damage and adducts ( Singh, 2000 ; Tice et al , 2000 ; Hermeto et al , 2014 ), may be repaired without becoming mutations ( Oliveira et al , 2007 ). In contrast, the micronucleus assay evaluates aneugenic and clastogenic activities that are not prone to repair.…”
Section: Discussionmentioning
confidence: 99%
“…Hermeto et al, have evaluated pH effects on genomic integrity in adipose-derived mesenchymal stem cells (MSCs); with the aim of evaluating two different comet assay protocols for genomic damage pattern analysis in MSCs derived from adipose tissue [50]. They found that in the pH>13 alkaline version detects damage in the form of single-strand breaks, double alkali-labile sites, cross-linking, and loss of excision.…”
Section: Recents Studies Using Comest Assaymentioning
confidence: 99%
“…They found that in the pH>13 alkaline version detects damage in the form of single-strand breaks, double alkali-labile sites, cross-linking, and loss of excision. The other version, pH=12 detects mainly single-and double-strand breaks [50].…”
Section: Recents Studies Using Comest Assaymentioning
confidence: 99%